Life saving tail amputation in an African lioness (Panthera leo L) in captivity (2015)
This paper reports surgical management of self- tail mutilation in an African lioness triggered by an irritation of unknown aetiology. The lioness was reported to have eaten up to two-third of its tail. Lack of darting facilities delayed quick intervention until the animal was lured with food bait into a restraint cage that enabled chemical restraint and surgical intervention. Tail amputation was performed as described for domesticated canine species. Healing was uneventful with animal returning to normal activities. Tail amputation is an uncommon procedure in wild species. Its curative indication was warranted in this case. There is need for storage of darting facilities in every zoological garden to aid quick intervention and preservation of animals especially endangered species in captivity